Adverse Effects of Methylglyoxal on Transcriptome and Metabolic Changes in Visceral Adipose Tissue in a Prediabetic Rat Model - Hüttl, Martina; Markova, Irena; Miklankova, Denisa; Makovicky, Pavol; Pelikanova, Terezie; Šeda, Ondrej; Šedová, Lucie; Malinska, Hana (Antioxidants (Basel, Switzerland), 2020)
Excessive methylglyoxal (MG) production contributes to metabolic and vascular changes by increasing inflammatory processes, disturbing regulatory mechanisms and exacerbating tissue dysfunction. MG accumulation in adipocytes leads to structural and functional changes. We used transcriptome analysis to investigate the effect of MG on metabolic changes in the visceral adipose tissue of hereditary hypetriglyceridaemic rats, a non-obese model of metabolic syndrome. Compared to controls, 4-week intragastric MG administration impaired glucose tolerance (p < 0.05) and increased glycaemia (p < 0.01) and serum levels of MCP-1 and TNFα (p < 0.05), but had no effect on serum adiponectin or leptin. Adipose tissue insulin sensitivity and lipolysis were impaired (p < 0.05) in MG-treated rats. In addition, MG reduced the expression of transcription factor Nrf2 (p < 0.01), which controls antioxidant and lipogenic genes. Increased expression of Mcp-1 and TNFα (p < 0.05) together with activation of the SAPK/JNK signaling pathway can promote chronic inflammation in adipose tissue. Transcriptome network analysis revealed the over-representation of genes involved in insulin signaling (Irs1, Igf2, Ide), lipid metabolism (Nr1d1, Lpin1, Lrpap1) and angiogenesis (Dusp10, Tp53inp1).
Keywords: methylglyoxal; insulin resistance; adipose tissue